2022
DOI: 10.1029/2022gl098186
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation in Northeast Mexico Primarily Controlled by the Relative Warming of Atlantic SSTs

Abstract: Reconstructing hydroclimate over the Common Era is essential for understanding the dominant mechanisms of precipitation change and improving climate model projections, which currently suggest Northeast Mexico will become drier in the future. Tree‐ring reconstructions have suggested regional rainfall is primarily controlled by Pacific sea‐surface temperatures (SSTs). However, tree ring records tend to reflect winter‐spring rainfall, and thus may not accurately record total annual precipitation. Using the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 100 publications
2
14
0
Order By: Relevance
“…SST changes that result in high interhemispheric thermal disparities shift the ITCZ's mean position towards the warmer hemisphere 69 . Lower SSTs across the (sub)tropical North Atlantic are less conducive to large-scale evaporation and the building of convective clouds along the ITCZ, resulting in a less coherent formation and reduced migration of the ITCZ into the northern hemisphere (NH), whereas higher SSTs have been found to increase summer precipitation in the northern Neotropics 70 .…”
Section: Classic Period Collapsementioning
confidence: 99%
“…SST changes that result in high interhemispheric thermal disparities shift the ITCZ's mean position towards the warmer hemisphere 69 . Lower SSTs across the (sub)tropical North Atlantic are less conducive to large-scale evaporation and the building of convective clouds along the ITCZ, resulting in a less coherent formation and reduced migration of the ITCZ into the northern hemisphere (NH), whereas higher SSTs have been found to increase summer precipitation in the northern Neotropics 70 .…”
Section: Classic Period Collapsementioning
confidence: 99%
“…δ 13 C values have been increasingly shown to reflect local water balance, with PCP and soil/vegetation changes all leading to higher δ 13 C values during drier periods 9,[41][42][43] . We suggest that a major driver of δ 13 C in CB2 is PCP, which occurs when there is reduced local water balance and is the result of enhanced CO 2 degassing and calcite precipitation in the epikarst 41 .…”
Section: Multiproxy Reconstruction Of Hydroclimate Variability In Ne ...mentioning
confidence: 99%
“…5 from 28 ). However, a recent speleothem study has suggested the dipole precipitation pattern is biased towards winter precipitation, and precipitation on annual timescales, and longer, may respond more in-phase throughout the region 9 . Unfortunately, the impact of SST variations on Mesoamerican hydroclimate patterns on millennial and orbital timescales is poorly constrained due to the paucity of records.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroclimate proxy evidence from CAM during the LIA, however, suggests significant heterogeneity, pointing to substantial spatial variability in hydroclimate. For example, proxy records from the northern Yucatán Peninsula (Hodell et al., 2005) and northern South America (Haug et al., 2001) indicate regional droughts at this time, suggesting a potential southward displacement of the rain belt, while proxy records from Belize (Asmerom et al., 2020), the highland regions of Guatemala (Stansell et al., 2020; Winter et al., 2020), central (Lozano‐García et al., 2007) and northeastern Mexico (Wright et al., 2022), and El Salvador (Wojewódka‐Przybył et al., 2022) do not support this pattern. This implies that ITCZ dynamics alone cannot explain the complex variability in CAM hydroclimate deduced from proxy records (Steinman et al., 2022).…”
Section: Introductionmentioning
confidence: 99%